Two Uncommon Causes of Guillain-Barré Syndrome: Hepatitis E and Japanese Encephalitis - Bandyopadhyay, Dhrubajyoti (Case Rep Neurol Med, 2015)
We are presenting two cases of Guillain-Barré syndrome where it is preceded by hepatitis E virus (HEV) and Japanese encephalitis virus (JEV) infection, respectively. Our first case is a forty-three-year-old nondiabetic, nonhypertensive female who was initially diagnosed with acute HEV induced viral hepatitis and subsequently developed acute onset ascending quadriparesis with lower motor neuron type of bilateral facial nerve palsies and respiratory failure. Second patient was a 14-year-old young male who presented with meningoencephalitis with acute onset symmetric flaccid paraparesis. After thorough investigations it was revealed as a case of Japanese encephalitis. Our idea of reporting these two cases is to make ourselves aware about this potential complication of these two common infections.